Coastal dune erosion under the influence of the Marie and Nadine storms in January 2022 on the Southern Baltic Sea coast - Łabuz, Tomasz Arkadiusz (Frontiers in Marine Science, 2025)
This paper examines the conditions leading to development and the course of the double storm surge event associated with cyclones Marie and Nadine in January 2022. The study also analyses the resulting changes of the dune coast following both surges. The findings are based on field measurements of morphological changes in beaches and dunes across various sections of the Polish coastline. The extent of coastal dune erosion was assessed with respect to storm surge parameters, including sea level height and wave run-up. Additionally, the relationship between beach height, wave run-up, and dune erosion volume was investigated. The maximum recorded sea level reached + 1.28 m, with wave run-up heights ranging between 3.0 and 3.3 m. Average erosion, measured as the retreat of the dune toe, was 4.3 m, though significantly higher retreat (4 to 8 m) was observed in areas where beach elevation was lower than the wave run-up. The most severe erosion, up to 8 m, occurred in cape-like sections where the coastline changes direction. Key factors influencing dune erosion volume included sea level and wave run-up heights, beach elevation, and the coast’s exposure to wind and wave action.